The Effects of Horizontal and Exchange Inequity on Tax Reporting Decisions. - Moser, Donald V.; Evans III, John H. (The Accounting Review, 1995)
Argues that the economic theory of tax reporting predicting taxpayers' responses depends on economic effects and perceptions of horizontal and exchange equity. Experiment resulting into conditions that influence the perceptions of inequity driving taxpayers' reporting decisions.